The Effect of Courses, Training and Entrepreneurship Seminars To Student’s Entrepreneurship Interest Of Study Program DIII Kebidanan STIKes Pamenang - Wulandari, Ratna Feti; Susiloningtyas, Luluk; Amperiana, Sukma (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Higher education has a role in fostering entrepreneurial interest for students by providing courses, training and seminars. This research aims to determine the effect of entrepreneurship courses, training and seminars on student interest in entrepreneurship. This quantitative research was descriptive approach. There were three variables, the independent variables were courses, training and entrepreneurship seminars. The dependent variable was entrepreneurship interest. This research started from September 2017 to September 2019. Data were collected from students of the DIII Midwifery Study Program at Stikes Pamenang and the sample size was 135 female students. The sampling technique used purposive sampling. The instrument for this study was questionnaire and it has been tested for validity and reliability. Data analysis using multiple linear regression analysis. The results stated that courses, training and seminars respectively affect student’s interest in entrepreneurship